The effect of road geometric (Gradient and curve) on friction value for interlocking concrete pavement - Henry Sidie, Sulang. (UNIMAS, 2005)
In general, the friction of interlocking concrete pavement is relatively high for all condition either wet or dry pavement. However, certain condition with a gradient and sharp curve involved, it could be dangerous in wet condition and might be given lower value of friction. This project was studied the effect of road geometric (gradient and curve) on friction value for interlocking concrete pavement at Jalan Reservoir Kuching and Jalan Dewan Bandaraya Kuching Utara (DBKU). The objectives of this project are to measure the loss of friction at interlocking concrete pavement and to evaluate the performance and their effect on vertical curve(gradient) and horizontal curve situation. This project was conducted by using “British Pendulum Tester”. Analysis data from friction test was then used to determine friction factor and skid number. In order to get the friction value, five spot pointsalong the road site for upgrade at Jalan Reservoir Kuching and four spot points for upgrade and downgrade were chosen at Jalan Dewan Bandaraya Kuching Utara (DBKU). Firstly, the result shown that the average of friction value at Jalan Reservoir Kuching was 46.6 and at Jalan Dewan Bandaraya Kuching Utara (DBKU) were 46.5 and 46.7 for upgrade and downgrade respectively, which is satisfactory in favorable circumstances as the data observation of FV was above 45 (TRL). Secondly, the friction factors values (FFV) werebetween ranges 0.2 to 0.39 at both locations, those values indicated the pavement surface is poor to fair (BS-5395). Lastly, the Skid Numbers (SN) for both locations was 31.2 and 31.0 and 31.3 respectively. Comparing to comment by Jayawickrama et al., 1996, the skid number indicated that monitor pavement frequently. As shown by the regression model generated,all the data from experimental concluded that friction value at interlocking concrete pavement increases with gradient on upgrades while on down grade concluded to the contrary.